2012
DOI: 10.5402/2012/436857
|View full text |Cite
|
Sign up to set email alerts
|

Remedial Prospective of Hippophae rhamnoides Linn. (Sea Buckthorn)

Abstract: Sea buckthorn (Hippophae rhamnoides L.) constitutes thorny nitrogen fixing deciduous shrub. Sea buckthorn(SBT) is primarily valued for its very rich vitamins A, B1, B12, C, E, K, and P; flavonoids, lycopene, carotenoids, and phytosterols. and therapeutically important since it is rich with potent antioxidants. Scientifically evaluated pharmacological actions of SBT are like inflammation inhibited by reduced permeability, loss of follicular aggregation of lymphocytes from the inflamed synovium and suppress lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 30 publications
(28 reference statements)
0
33
0
Order By: Relevance
“…One of the main components contributing to this effect is quercetin that induces apoptosis in cancer cells. The best effect has been reported in relation to the treatment of patients with colon cancer, leukaemia, and prostatic carcinoma (Patel et al 2012). Other studies suggest that sea buckthorn oil alleviates haematological damage caused by chemotherapy, such as part of treatment of leukaemia .…”
Section: Anticarcinogenic Activitymentioning
confidence: 75%
See 1 more Smart Citation
“…One of the main components contributing to this effect is quercetin that induces apoptosis in cancer cells. The best effect has been reported in relation to the treatment of patients with colon cancer, leukaemia, and prostatic carcinoma (Patel et al 2012). Other studies suggest that sea buckthorn oil alleviates haematological damage caused by chemotherapy, such as part of treatment of leukaemia .…”
Section: Anticarcinogenic Activitymentioning
confidence: 75%
“…Their main function is suppression of platelet aggregation induced by collagen, probably by inhibition of the thyrosine kinase activity (Patel et al 2012). Another substance significantly contributing to platelet aggregation is sitosterol (Johansson et al 2000).…”
Section: Platelet Aggregationmentioning
confidence: 99%
“…A recent study by Kruczek et al [36] has showed the antioxidant capacity of crude extracts containing carotenoids from the berries of various cultivars of Seabuckthorn (Hippophae rhamnoides L.). Strong correlation was also observed between DPPH scavenging activity and total phenolic content from all Vinay Kant, et al: Antioxidant potential of seabuckthorn pomace the extracts of two species of sea-buckthorn; namely, Hippophae salicifolia D. Don and Hippophae rhamnoides L. [37] In review of Patel et al, [38] it has been described that seabuckthorn reduced recurrence of angina, ischemic electrocardiogram which might be due to decreased myocardial oxygen consumption and inhibition of platelet aggregation induced by collagen. So, in addition of the antioxidant properties of these extract, they can be validated for the prevention of these complications.…”
Section: Reducing Power Capabilitymentioning
confidence: 96%
“…SBT is thorny nitrogen fixing deciduous shrub native to Europe and Asia, which is used as a medicinal plant in Tibetan and Mongolian traditional medicines (Lu, 1992;Patel et al, 2012;Rousi et al, 1971). Since the 1950's, many curative preparations of SBT have been clinically used to treat radiation damage, burns, oral inflammation and gastric ulcers in China and the former Soviet Republics (Fu et al, 1993;Geetha et al, 2002;Isoherranen et al, 1999;Mereish et al, 1991).…”
Section: Sea Buckthorn (Sbt)mentioning
confidence: 99%